Study of the flameless combustión mode in presence of the thermal load fluctuation (2017)
The present study evaluated numerically and experimentally in a 20 kW furnace (using natural gas as fuel and with an equivalent ratio of 1.2) the stability of the flameless combustion regime due to the fluctuation of the thermal load through the use of different air flow (43 scfm, 63 scfm y 83 scfm) and an Air-Helium mixture (Air 82.02 scfm and Helium 7.06 scfm); the last one it was used to evaluate the behavior of the system in the face of an increase in the load fluid specific heat capacity. The study was divided in two parts, numerical simulation and experimental phase. From the numerical simulation was calculated the temperature profile, CO profile, the recycle ratio Kv and the mass of flue gases recirculated. In the experimental phase the temperature profiles obtained showed a decrease in the temperature of the combustion chamber as the load air flow increased however, this decrease did not affect the thermal uniformity inside of the furnace. Furthermore the useful efficiency showed an increase when went over from a load air of 43 scfm to 63 scfm, followed by a decrease of it with the other load flows.